Voices of Informal Caregivers and Community Stakeholders: Whether and How to Develop an Informal Caregiver Training Program - Phillips, Sara S. (J Community Health, 2016)
Our primary objective was to gather pilot data from caregivers and stakeholders to guide the development of a training program to assist informal caregivers in re-entering the job market. The goal of the program would be to help caregivers rebound from their incurred economic burden by transitioning into a paid caregiving or other health-service role. The economic burden they bear often necessitates a return to the workforce following caregiving; yet the act of returning is complicated by an extended absence from the workforce and a lack of experience in other verifiably skilled and paid roles. We interviewed 37 stakeholders and 25 caregivers of a chronically or terminally ill family member or friend in a suburban collar county close to Chicago. The interview questions considered the economic impact of illness, as well as the feasibility, logistics, and options of a training program for caregivers. Our data gathered from caregivers and leaders within this community support the acceptability of such a training program for informal caregivers, and also provide practical advice for development and implementation related to training cost, length, content, and instructional practices.